The COVID-19 Pandemic and Reflections on the Importance of Reintegration Strategies for Returnee Migrant Workers - Kusumo, Rani Andriani Budi; Kurnia, Ganjar; Setiawan, Iwan; Tirtosudarmo, Riwanto (Two Homelands, 2023)
This study aims to analyze the reintegration problems faced by Indonesian Migrant Workers (IMWs). This study was conducted using a qualitative design in Indramayu Regency, Indonesia. Data was collected from IMWs who returned during the pandemic, brokers, and the Indonesian Migrant Workers Protection Agency (BP2MI) staff and analyzed descriptively. The results showed that returnee migrants face problems such as the inability to manage remittances, poor investment choices, and the inability to run a business. A comprehensive reintegration policy is needed starting from pre-departure until the migrants return to their country of origin.